Mapping the Potential of Organic Waste as a Bioconversion Substrate for Black Soldier Fly Larvae (BSFL) in Surabaya City and Sidoarjo Regency - Fitriana, Aulia Rodlia; Bagastyo, Arseto Yekti; Warmadewanthi, IDAA; Hanh, Dang Vu Bich; Ursada, Riang (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Waste management remains a critical challenge in Indonesia, particularly in urban areas. Bioconversion using Black Soldier Fly Larvae (BSFL) presents a sustainable solution for transforming organic waste into high-value biomass rich in protein and fat. The objective of this study was to investigate the potential utilization of organic waste from markets, bakeries, and rejected products from the food and beverage (F&B) industry (specifically creamer and milk), as BSFL substrates, while mapping the existing bioconversion sites. Data was collected through interviews, observations, and field measurements. Primary data included location details, technical specifications, implementation constraints, and BSFL bioconversion sites. Waste composition was analyzed via Loud Count Analysis during a 4-day sampling period. This research was conducted in Surabaya City and its surroundings. The results indicate that market waste mostly consists of dark green vegetables (26.5%), other vegetables (64.1%), and year-round fruits (53.9%). Furthermore, the daily average rejected bread is 2.6-2.7 kg. Rejected foods and beverages include creamers, liquids, and sweetened condensed milk. The facility processes 16.16 tons/day of substrate potential, producing 44.61 tons fresh larvae and 53.85 tons frass, with profits of IDR 58.1-969.6 million. The findings demonstrate significant potential for utilizing local organic waste as BSFL substrates in the study area.